-2(3x-1)+16=0

Simple and best practice solution for -2(3x-1)+16=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(3x-1)+16=0 equation:



-2(3x-1)+16=0
We multiply parentheses
-6x+2+16=0
We add all the numbers together, and all the variables
-6x+18=0
We move all terms containing x to the left, all other terms to the right
-6x=-18
x=-18/-6
x=+3

See similar equations:

| -11-3d=19 | | 5-9=w/6 | | -7j+6=111 | | 13+(p/3)=‐4 | | -361/3+x=20 | | 34-f=43 | | -71=-6-5a | | -28=-y+4 | | 6(n-9=27 | | -3x=1=-23 | | w+49+w+2+w=180 | | F(5)=-2x-7 | | -21=t18 | | –11n−–8=19 | |  3(x + 13) − 5  =  3x − 4 | | 2(9-x)=3(x-16) | | q-12=19 | | 3xx3=360 | | Xx-5=-115 | | 2(x+2)=(4x-16) | | 13-n=26 | | 3x*3=360 | | 19-d=27 | | 4742-x=3497 | | 33=x/100 | | 47-p=55 | | (1/5)y+8=-7 | | -2(x8)+4x=-12 | | ​2(p+1)=24​ | | 230p=5 | | 3(7v-1)=81 | | 5/13=3/x |

Equations solver categories